2015
DOI: 10.1161/circinterventions.114.002358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulmonary Hypertension Hemodynamic Presentation on Clinical Outcomes in Patients With Severe Symptomatic Aortic Valve Stenosis Undergoing Transcatheter Aortic Valve Implantation

Abstract: P ulmonary hypertension (PH) frequently coexists with severe aortic stenosis (AS) and confers a worse prognosis.1,2 Transcatheter aortic valve implantation (TAVI) is an alternative therapeutic modality to surgical aortic valve replacement (SAVR) for patients with symptomatic severe AS who are either inoperable or high risk for conventional SAVR.3-5 Patient selection for TAVI relies on clinical and anatomic factors, and risk assessment is a critical component of the procedural planning. 6 Previous studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
153
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(169 citation statements)
references
References 37 publications
11
153
3
2
Order By: Relevance
“…2 We observed that patients with isolated postcapillary PH had clinical outcomes similar to patients without PH, whereas combined postcapillary and precapillary PH was a strong predictor of all-cause mortality at 1 year after adjustment for several comorbidities. 2 We agree with Dr Bishu 1 that raw pulmonary artery systolic pressure (PASP) estimates alone provide prognostic information among patients with severe aortic stenosis undergoing both TAVI and surgical aortic valve replacement as has been shown in several studies.3-6 However, raw PASP estimates provide no information whatsoever about the likely cause of PH. Conversely, by stratifying patients according to hemodynamic presentation, it is possible to differentiate PH because of left heart disease (ie, postcapillary PH or group 2 PH) from other PH subgroups (ie, precapillary PH-groups 1, 3, 4, and 5 PH).…”
mentioning
confidence: 68%
“…2 We observed that patients with isolated postcapillary PH had clinical outcomes similar to patients without PH, whereas combined postcapillary and precapillary PH was a strong predictor of all-cause mortality at 1 year after adjustment for several comorbidities. 2 We agree with Dr Bishu 1 that raw pulmonary artery systolic pressure (PASP) estimates alone provide prognostic information among patients with severe aortic stenosis undergoing both TAVI and surgical aortic valve replacement as has been shown in several studies.3-6 However, raw PASP estimates provide no information whatsoever about the likely cause of PH. Conversely, by stratifying patients according to hemodynamic presentation, it is possible to differentiate PH because of left heart disease (ie, postcapillary PH or group 2 PH) from other PH subgroups (ie, precapillary PH-groups 1, 3, 4, and 5 PH).…”
mentioning
confidence: 68%
“…It operates the continuum between left ventricular dysfunction and right heart failure in the context of pressure overload: indeed, the backward transmission of the elevated pressures in the hypertrophic left ventricle promotes the remodelling of pulmonary vasculature. The presence of pulmonary hypertension affects the prognosis of patients with severe AS irrespective of the treatment 7,10,11 . In this context, we sought to investigate whether other invasive haemodynamic parameters, among those mirroring the pathophysiology of the valvular disease, could be related to mortality after TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, clinical characteristics and comorbidities at baseline represent the variables with greatest prognostic weight in recently developed scores to predict early and late mortality after TAVI 22 . Previous investigations by our group focused on the effect of haemodynamic patterns of pulmonary hypertension or low-flow, low-gradient aortic stenosis on clinical outcomes after TAVI 7,23 . Instead, the present analysis sought to determine whether preoperative RHC provides additional prognostic value on top of standard, non-invasive evaluation including clinical and echocardiographic parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the right ventricle's functional adaptation to afterload may matter more to prognosis than only PH and related vascular gradients [21,22], and measurements for phenotyping do not solely qualify by prognostic capability [22,23]. In the meantime, several studies have nevertheless confirmed the impact on outcome of an increased DPG in PH-LHD [24][25][26][27].…”
mentioning
confidence: 99%